EFEK IBUPROFEN ORAL TERHADAP PERUBAHAN BERAT BADAN PADA MENCIT BETINA - Anindya Marcha Angelina Djianto; Tri Hartini Yuliawati; Sri Ratna Dwiningsih; Widjiati Widjiati (Universitas Airlangga, Surabaya, Indonesia, 2019)
Background: Ibuprofen is one of the most used non-steroidal anti-inflammatory drugs (NSAID) due to its ease of access without the need of prescription. However, ibuprofen may cause side effects associated with gastrointestinal mucosal injury. The discomfort caused when eating may cause nausea and loss of appetite which leads to weight loss. Objective: This study was done to prove changes in body weight after treatment of oral ibuprofen using mice as test subjects. Material and method: This study used pre-test post-test control group design. 33 female BALB/c mice were grouped into 3 groups (P1, P2, P3). P1 is a control group which was given aquadest as placebo, P2 was given 52 mg/kg body weight of oral ibuprofen and P3 was given 104 mg/kg body weight of oral ibuprofen. Treatment lasted for 15 days. Results were analyzed using Kruskal-Wallis test and Mann-Whitney U test in IBM SPSS Statistics 22. Result: 80% of the mice had their body weights decreased with an average decrease of 0.91 g (±2.26) in group P1, average decrease of 2.2 g (±2.15) in P2, and average decreased of 4.11 g (±2.62) in P3. Statistical analysis showed that body weight changes of group P3 has significant difference (p = 0.009) compared to P1 and P2. Conclusion: It can be concluded that 104 mg/kg dose of oral ibuprofen caused a decrease in body weight of female mice.